Field Evaluation Of The Fruit Fly Food Bait, Success Appat® (Gf-120), And Waste Brewers’ Yeast (Wby) Against Fruit Flies (Diptera: Tephritidae) In Mango Orchards - Banini, C.K. (University of Ghana, 2012)
The efficacy of Waste Brewers‟ Yeast (WBY) + Imidacloprid (Akape®) (insecticide) as food bait was compared with the novel fruit fly food bait, commercially available as SUCCESS APPAT® (GF-120) in the field as attractants for the management of fruit flies in mango orchards at the Coastal Savanna ecological zone for two major seasons (2010/2011 and 2011/2012). Randomised Complete Block Design was used and a meter square of foliage of every tree in the WBY and GF-120 plots was spot-treated with about 50-60 mls coarse spray mix of the two products weekly. Control plots received no application or treatment. The population dynamics of the fruit flies were monitored on weekly basis with three different lures, Methyl eugenol (ME), Terpinyl acetate (TA) and Trimedlure (TML) in improvised plastic bottle traps in each plot. Prior to treatment application, baseline survey was carried out for three weeks to determine the fruit fly species and fly density levels in the three study sites (Ayenya 1, Akorley 1 and Akorley 2). After 6-8 weeks of treatment, 30 matured fruits were sampled from each plot, weighed and incubated on sterilised sand to determine their levels of infestation by flies. This was repeated at the end of the fruiting season, and for the first and second seasons. A total of 22,652 organisms were collected during the study period, out of which 22,355 were fruit flies and 297 non-target organisms. The fruit flies constituted 98.69%, while the non-targets were 1.31%. The pre-treatment periods for season one (SO) and season two (ST) recorded 8,621 and 13,734 fruit flies, respectively. . Four fruit fly species, belonging to two genera, were identified in the collections. These were Bactrocera invadens Drew, Tsuruta and White (Africa Invader fly), Ceratitis cosyra Walker (Mango fruit fly) Ceratitis capitata (Wiedemann) (Mediterranean fruit fly), and Ceratitis ditissima Munro (West Africa citrus fly). Total fly catches were significantly different for the various lures, with Methyl Eugenol traps recording the highest (1285.67 ± 118.41) at Ayenya 1. However, there were no significant differences between trap catches of TML and TA traps. The relative fly densities (number of flies per trap per day, F/T/D) ranged from 0.007-10.192 and 0.004-11.666 flies per trap per day in first and second seasons respectively. The highest number of puparia was recovered from the Control plots which recorded 163 and the least was from WBY treated plots 63 and the GF-120 recorded 84. The only non-tephritid species that emerged was identified to be Carpophilus bipustulatus (Heer) (Coleoptera: Nitidulidae). The highest infestation level (1.0) was recorded by the Control; followed by GF-120 (0.67) and WBY (0.54). This resulted into fruit infestation reduction levels of 33% and 46% by GF-120 and WBY, respectively compared to the Control plot. WBY in its crude form was equally effective and attracted the same fruit fly species as the standard SUCCESS APPAT® (GF120) though in varied proportions.
Thesis (MPhil)
Keywords: Fruit Fly Food Bait; Success Appat® (Gf-120); Waste Brewers’ Yeast (Wby); Fruit Flies (Diptera: Tephritidae); Mango Orchards